2021
DOI: 10.3892/etm.2021.10984
|View full text |Cite
|
Sign up to set email alerts
|

PINCH1 knockout aggravates myocardial infarction in mice via mediating the NF‑κB signaling pathway

Abstract: Myocardial infarction (MI), the leading cause of death among patients with cardiovascular diseases, is characterized by acute cardiac muscle injury due to severe impairment of the coronary blood supply, which may lead to cardiogenic shock and cardiac arrest. Particularly interesting new cysteine histidine rich 1 (PINCH1) protein, a key component of the integrin signaling pathway, interacts with several proteins and serves a vital role in numerous cellular processes, including cytoskeleton remodeling, cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…Third and most importantly, pharmacological inhibition of TNFα largely mitigated the spontaneous and LSI-induced degenerative lesions caused by Pinch loss in dKO mice. Consistent with results from this study, Wang et al have demonstrated that genetic ablation of Pinch1 in cardiomyocytes activated the NFκB signaling pathway, resulting in excessive production of TNFα and cardiac injury [ 59 ]. It has been demonstrated that TNFα promotes DDD progression by causing ECM degradation, amplifying the inflammatory responses, and inducing IVD cell apoptosis [ 51 , 60 ].…”
Section: Discussionsupporting
confidence: 90%
“…Third and most importantly, pharmacological inhibition of TNFα largely mitigated the spontaneous and LSI-induced degenerative lesions caused by Pinch loss in dKO mice. Consistent with results from this study, Wang et al have demonstrated that genetic ablation of Pinch1 in cardiomyocytes activated the NFκB signaling pathway, resulting in excessive production of TNFα and cardiac injury [ 59 ]. It has been demonstrated that TNFα promotes DDD progression by causing ECM degradation, amplifying the inflammatory responses, and inducing IVD cell apoptosis [ 51 , 60 ].…”
Section: Discussionsupporting
confidence: 90%